2021
DOI: 10.1149/1945-7111/ac0f86
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Exploration of Coupled Transient Mechanical and Electrochemical Behaviors in Lithium Ion Batteries

Abstract: Lithium-ion batteries represent a dominant technology in the current energy storage market. However, many aspects of these batteries are still poorly understood, and proper engineering of these aspects will lead to increased cycle life and performance parameters. In particular, the electrode/electrolyte interface is still an actively researched topic and is notoriously difficult to study. An ultrasound acoustic characterization technique is introduced to probe the electrode/electrolyte interface in operando us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…[48][49][50] In fact, it has been shown that changes in the graphite negative electrode and the graphite/electrolyte interface dominate the ultrasonic response of the battery, as the changes in the positive electrode material and thickness are negligible compared to that of the anode. [51] Most literature has focused on analyzing waves that propagate throughout the flat, layered structure of pouch-type LIBs. However, alternative methodologies, such as guided waves, leverage the battery geometry as a waveguide, thereby minimizing energy loss and covering a substantial portion of the surface area.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50] In fact, it has been shown that changes in the graphite negative electrode and the graphite/electrolyte interface dominate the ultrasonic response of the battery, as the changes in the positive electrode material and thickness are negligible compared to that of the anode. [51] Most literature has focused on analyzing waves that propagate throughout the flat, layered structure of pouch-type LIBs. However, alternative methodologies, such as guided waves, leverage the battery geometry as a waveguide, thereby minimizing energy loss and covering a substantial portion of the surface area.…”
Section: Introductionmentioning
confidence: 99%
“…16 Based on that ultrasonic methods for SoC estimation have been developed and have soon become a hot spot in this field. [17][18][19][20][21][22] However, there is still a fundamental problem unsolved in this field: is the measured ultrasonic response to SoC due to anode or cathode change? In most previous literature reports, the LIB cells were treated as a whole, because the cells are composed of multiple layers of cathodes, anodes, separators and current collectors.…”
Section: Introductionmentioning
confidence: 99%
“…16 Based on that ultrasonic methods for SoC estimation have been developed and have soon become a hot spot in this field. 17–22…”
Section: Introductionmentioning
confidence: 99%
“…This results in considering both the electrochemical and mechanical properties of the electrode during the earliest stages, and information is needed on relevant process-property coupling. [26][27][28][29] As an example, both energy density and mechanical strength of sintered electrodes can be enhanced by reducing electrode porosity. 30 However, reduction in porosity increases pore tortuosity, 31 enhancing resistance to ion transport through the electrode microstructure and reducing capacity delivered at increased rates and roundtrip efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Sintered electrodes must satisfy the multifunctional role of meeting both electrochemical and mechanical demands of the brittle porous thin film of active material. This results in considering both the electrochemical and mechanical properties of the electrode during the earliest stages, and information is needed on relevant process–property coupling 26‐29 . As an example, both energy density and mechanical strength of sintered electrodes can be enhanced by reducing electrode porosity 30 .…”
Section: Introductionmentioning
confidence: 99%